A survey study on safety and microbial quality of "gluten-free" products made in Italian pasta factories. (March 2017) - Losio, Marina-Nadia; Dalzini, Elena; Pavoni, Enrico; Merigo, Daniela; Finazzi, Guido; Daminelli, Paolo
Abstract: The rising prevalence of celiac disease leads to an increased demand of "gluten-free" products. A survey study on the gluten content and on the microbiological quality of "gluten-free" flour, and processing flour products, was carried out from 2010 to 2015 in Northern Italy. Overall 12, 419 samples were analyzed, and 94.7% contained a gluten concentration less than 5 mg kg −1 (lower limit of detection). Only 0.1% of samples showed a gluten concentration above 80 mg kg −1 (maximum limit of detection). In the remaining 5.2%, the gluten concentration was between 5 and 80 mg kg −1, underlining how a gluten-free diet completely devoid of gluten is unrealistic. The microbiological quality of these products was investigated. Overall, the majority of samples revealed microbial loads of less than 1 l g CFU g −1 (lower limit of detection). High levels of spoilage bacteria were found in egg-containing products. Total mesophilic bacteria were counted in all analyzed food categories with concentrations up to about 6, 8 and 9 l g CFU g −1 in dry pasta, flours and egg products respectively. Listeria monocytogenes was found only in one sample, whereas Salmonella spp. was never found. Buckwheat flour was the most frequently contaminated product by presumptive Bacillus cereus, with a prevalence of 12.5%. Also, a contamination by Coagulase-Positive Staphylococci was found during this investigation, especially in buckwheat dry pasta and flour and in egg dry pasta, with a prevalence of 54.7%. This study aimed to enhance the knowledge about the "gluten-free" products which are still poorly studied, even if their impact on the food market is increasingly considerable. Highlights: We investigated the safety and the hygiene quality of "gluten-free" products. Traces of gluten were found only in 0.8% of samples. The majority of samples indicated low bacterial contamination levels. High values of spoilage bacteria were counted in egg-containing products. Bacillus cereus and Coagulase-Positive Staphylococci were found in same products.